2014
DOI: 10.1002/jat.3039
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology‐based cancer causation analysis of CoCr‐containing hip implants: a quantitative assessment of genotoxicity and tumorigenicity studies

Abstract: In this paper, quantitative methods were used to evaluate the weight of evidence regarding a causative relationship between cobalt-chromium (CoCr)-containing hip implants and increased cancer risk. We reviewed approximately 80 published papers and identified no-observed-adverse-effect level (NOAEL) and/or lowest-observed-adverse-effect level (LOAEL) values for specific endpoints of interest: genotoxic effects from in vitro studies with human cell lines as well as genotoxicity and tumor formation in animal bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 163 publications
0
35
0
1
Order By: Relevance
“…It is also found to have an excellent combination of material toughness and yield strength, ductility, and hardness (Navarro, Michiardi, Castaño, & Planell, 2008). However, adding more than 30% chromium makes this alloy hard to cast and results in a brittle phase (Christian, Oliver, Paustenbach, Kreider, & Finley, 2014). However, adding more than 30% chromium makes this alloy hard to cast and results in a brittle phase (Christian, Oliver, Paustenbach, Kreider, & Finley, 2014).…”
Section: Cobalt-chromium Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also found to have an excellent combination of material toughness and yield strength, ductility, and hardness (Navarro, Michiardi, Castaño, & Planell, 2008). However, adding more than 30% chromium makes this alloy hard to cast and results in a brittle phase (Christian, Oliver, Paustenbach, Kreider, & Finley, 2014). However, adding more than 30% chromium makes this alloy hard to cast and results in a brittle phase (Christian, Oliver, Paustenbach, Kreider, & Finley, 2014).…”
Section: Cobalt-chromium Alloymentioning
confidence: 99%
“…vance between particles and complications has not been thoroughly evaluated and Christian et al suggested that the Co/Cr concentrations in the blood and tissue of MoM implant patients are too low to increase the risk of systemic disease(Christian et al, 2014).…”
mentioning
confidence: 99%
“…One study analyzed over 80 published papers to determine if there is a relationship between CoCr implants and an increase in cancer. They found that the Co and Cr ion concentration in the bodies of those with meal‐on‐metal articulations were far too small to substantially increase the risk of developing systemic cancer . In vitro and in vivo assays showed that DNA defects would be very unlikely to occur due to the increase in Co or Cr ion concentration as a result of a MOM articulation .…”
Section: Metals Utilized During Tjrmentioning
confidence: 99%
“…They found that the Co and Cr ion concentration in the bodies of those with meal‐on‐metal articulations were far too small to substantially increase the risk of developing systemic cancer . In vitro and in vivo assays showed that DNA defects would be very unlikely to occur due to the increase in Co or Cr ion concentration as a result of a MOM articulation . Moreover, in 40 tumor bioassays where Co and Cr ion concentrations were significantly higher than those in hip implants, none reported a significant increase in systemic cancer .…”
Section: Metals Utilized During Tjrmentioning
confidence: 99%
“…Après le retrait de la prothèse chez les patients intoxiqués par le cobalt, l'état clinique s'améliore même si certains symptômes peuvent persister [22,24]. Plusieurs études ont démontré que le risque cancérogène n'est pas significativement différent de celui de la population générale [7,26]. En raison du passage transplacentaire du cobalt au cours de la grossesse, le risque pour la descendance est suspecté même s'il n'est pas prouvé.…”
Section: Synthèse Revuesunclassified